Evaluating the Impact of AI-Driven Decision Support Systems on Organizational Performance in the Digital Economy - Soleman (Universitas Mohammad Husni Thamrin, 2026)
This study aims to evaluate the impact of AI-driven Decision Support Systems (AI-DSS) on organizational performance within the context of the digital economy. Specifically, the research examines how the adoption of AI-based decision-support technologies influences decision quality, operational efficiency, strategic agility, and overall organizational effectiveness. Employing a quantitative research design, the study collected primary data through a structured questionnaire distributed to managers and decision-makers across various industries that have implemented AI-DSS. A total of valid responses were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to assess both direct and indirect relationships among variables. The data analysis focused on measuring the reliability and validity of constructs, hypothesis testing, and the explanatory power of AI-DSS in predicting organizational performance outcomes. The findings indicate that AI-driven decision support systems have a significant and positive effect on organizational performance, primarily through improvements in decision accuracy, speed, and data-driven strategic alignment. Moreover, the results reveal that organizational digital capability acts as a partial mediator, strengthening the relationship between AI-DSS adoption and performance outcomes. This study contributes to the growing body of literature on digital transformation by providing empirical evidence on the strategic value of AI-enabled decision support systems and offers practical implications for organizations seeking to enhance competitiveness in the digital economy.